Challenges and Progress in Nonsteroidal Anti-Inflammatory Drugs Co-Crystal Development - Nugrahani, Ilma (Molecules, 2021)
Co-crystal innovation is an opportunity in drug development for both scientists and industry. In line with the “green pharmacy” concept for obtaining safer methods and advanced pharmaceutical products, co-crystallization is one of the most promising approaches to find novel patent drugs, including non-steroidal anti-inflammatory drugs (NSAID). This kind of multi-component system improves previously poor physicochemical and mechanical properties through non-covalent interactions. Practically, there are many challenges to find commercially viable co-crystal drugs. The difficulty in selecting co-formers becomes the primary problem, followed by unexpected results, such as decreased solubility and dissolution, spring and parachute effect, microenvironment pH effects, changes in instability, and polymorphisms, which can occur during the co-crystal development. However, over time, NSAID co-crystals have been continuously updated regarding co-formers selection and methods development.